UNDERSTANDING HOW CANCER PATIENTS ACTUALISE, RELINQUISH, AND REJECT ADVANCE CARE PLANNING: IMPLICATIONS FOR PRACTICE. Issue 2 (1st June 2013) - Michael, N; Stepanov, N; Spruyt, O; Pollard, A; Clayton, J; O'Callaghan, C
Abstract : Background: Although advance care planning (ACP) is recognised as intégral to quality cancer care, it remains poorly integrated in many settings. Given cancer patients' unpredictable disease trajectories and equivocal treatment options, a disease specific ACP model may be necessary. Aims: To examine how Australian cancer patients consider ACP and inform the development of an Australian Cancer Centre's ACP programme. Methods: A constructivist research approach drawing on the Medical Research Council framework for complex interventions. Participants described their initial understanding of ACP, received ACP information, and finally completed a semi-structured interview assisted by the vignette technique. Qualitative inter-rater reliability was integrated. Results: Twenty-nine patients from the lung and gastro-intestinal tumour streams were approached with 18 completing the study. Participants initially had scant knowledge of ACP. On obtaining further information, their responses indicated that: For cancer patients, ACP is an individualised, dynamic, and shared process characterised by myriad variations in choices to actualise, relinquish, and/or reject its individual components. Actualisation of each component involves considering, possibly conversing about, planning, and communicating a decision, usually iteratively. Reactions can change over time and are informed by values, memories, personalities, health perceptions, appreciation of prognoses, and trust or doubts in their substitute decision makers. Discussion/Conclusion: Findings endorse the value of routinely, though sensitively discussing ACP with cancer patients at various times points across their disease trajectory. Nonetheless, ACP may also be relinquished or rejected and ongoing offers for ACP in some patients may be offensive to their value system.